The Evolving Telomeres - Kurt Runge (Frontiers Research Topics, 2016)
What controls the different rates of evolution to give rise to conserved and divergent proteins and RNAs? How many trials until evolution can adapt to physiological changes? Every organism has arisen through multiple molecular changes, and the mechanisms that are employed (mutagenesis, recombination, transposition) have been an issue left to the elegant discipline of evolutionary biology. But behind the theory are realities that we have yet to ascertain: How does an evolving cell accommodate its requirements for both conserving its essential functions, while also providing a selective advantage? In this volume, we focus on the evolution of the eukaryotic telomere, the ribo-nuclear protein complex at the end of a linear chromosome. The telomere is an example of a single chromosomal element that must function to maintain genomic stability. The telomeres of all species must provide a means to avoid the attrition from semi-conservative DNA replication and a means of telomere elongation (the telomere replication problem). For example, telomerase is the most well-studied mechanism to circumvent telomere attrition by adding the short repeats that constitutes most telomeres. The telomere must also guard against the multiple activities that can act on an unprotected double strand break requiring a window (or checkpoint) to compensate for telomere sequence loss as well as protection against non-specific processes (the telomere protection problem). This volume describes a range of methodologies including mechanistic studies, phylogenetic comparisons and data-based theoretical approaches to study telomere evolution over a broad spectrum of organisms that includes plants, animals and fungi. In telomeres that are elongated by telomerases, different components have widely different rates of evolution. Telomerases evolved from roots in archaebacteria including splicing factors and LTR-transposition. At the conserved level, the telomere is a rebel among double strand breaks (DSBs) and has altered the function of the highly conserved proteins of the ATM pathway into an elegant means of protecting the chromosome end and maintaining telomere size homeostasis through a competition of positive and negative factors. This homeostasis, coupled with highly conserved capping proteins, is sufficient for protection. However, far more proteins are present at the telomere to provide additional species-specific functions. Do these proteins provide insight into how the cell allows for rapid change without self-destruction?